2018
DOI: 10.2196/mhealth.8619
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Health App Use Among Older Adults in Germany: National Survey

Abstract: BackgroundHealth apps are increasingly becoming an integral part of health care. Especially in older adults, the self-management of chronic diseases by health apps might become an integral part of health care services.ObjectiveThe aim of this explorative study was to investigate the prevalence of health app use and related demographic factors, as well as health status among older adults in Germany.MethodsA nationwide postal survey was conducted. Of the 5000 individuals contacted, a total of 576 participants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 21 publications
9
108
1
6
Order By: Relevance
“…Similarly, reports for health apps, including mental health related, show limited downloads and poor retention, especially outside of clinical trials and research settings. In national surveys in Germany, 20.5% of adult smartphone users 35 years or older, and 16.5% older adults used a health app (Ernsting et al 2017;Rasche et al 2018). In a national survey of smartphone users in the US, 58% had downloaded a health app but about half had stopped using it (Krebs and Duncan 2015).…”
Section: App Retention Ratesmentioning
confidence: 99%
“…Similarly, reports for health apps, including mental health related, show limited downloads and poor retention, especially outside of clinical trials and research settings. In national surveys in Germany, 20.5% of adult smartphone users 35 years or older, and 16.5% older adults used a health app (Ernsting et al 2017;Rasche et al 2018). In a national survey of smartphone users in the US, 58% had downloaded a health app but about half had stopped using it (Krebs and Duncan 2015).…”
Section: App Retention Ratesmentioning
confidence: 99%
“…However, after self-training and getting help from family, the positive effects of telemedicine were evident because patients independently used the portable smartphones [14]. In this research, both groups showed improved blood glucose and HbA1c levels.…”
Section: Discussionmentioning
confidence: 59%
“…Deskriptive Ergebnisse sowie eine detailliertere Beschreibung des Fragebogens finden sich bei Mertens et al (2017). Vertiefende Analysen dieser Studie sind bei Rasche et al (2018), Bröhl et al (2018) und Theis et al (2018) nachzulesen. Die Studie wird alle drei Jahre erneut durchgeführt werden, um auf Anforderungs-und Parameteränderungen in der Entwicklung der Zielgruppe reagieren zu können.…”
Section: Datenbasierter Hintergrundunclassified